Cognitive Relevance and Linguistic Suggestion in Questioning Strategies to Enhance Witness Honesty in Indonesian Courtroom Interaction - Priadi, Arum; Ilham, Ilham (Universitas Muhammadiyah Mataram, 2025)
This study aims to examine how integrating Relevance Theory (RT) and Hypnotic Language Patterns can enhance witness honesty and recall through ethically suggestive questioning in Indonesian criminal trials. Courtroom questioning is a linguistically and cognitively complex act that mediates the production and evaluation of witness testimony. Despite its central role in shaping evidentiary narratives, questioning in Indonesian courtrooms remains predominantly procedural, with limited attention to the psychological and inferential dimensions of communication. Adopting a qualitative cognitive–pragmatic approach, the study draws on discourse and thematic analyses of two Indonesian criminal trials to explore how questioning strategies function at the intersection of cognition, inference, and judicial ethics. The analysis identifies nine recurrent questioning techniques, including soft suggestion, presupposition, and commitment framing. Findings indicate that soft suggestion (15.1%) and commitment framing (15.15%) reduce cognitive resistance and foster more detailed, coherent recollection. The results suggest that linguistic suggestion, when aligned with principles of cognitive relevance, can establish psychological safety and interpretive precision without compromising judicial neutrality. By conceptualizing courtroom questioning as guided cognition, this study advances forensic pragmatics through an integrated framework linking linguistic ethics, cognitive accessibility, and evidentiary reliability within a culturally contextualized legal setting.